An atypical metallic bezoar on imaging - Thacker, Nidhi N.; Padhiyar, Charmy; Kamat, Ritesh D. (International Journal of Research in Medical Sciences, 2026)
Laparoscopic fundoplication with mesh reinforcement is an established surgical treatment for gastroesophageal reflux disease and large hiatal hernias. Although long-term outcomes are generally favorable, delayed postoperative complications may occur, including wrap migration, recurrent hiatal hernia, mesh-related sequelae. We report a case of severe fundoplication failure with recurrent hiatal hernia complicated by metal bezoar-like intraluminal lesion with impregnated food particles on CT. This case highlights the importance of recognizing misleading intraluminal appearances on cross-sectional imaging to avoid diagnostic pitfalls and facilitate timely management.